2017
DOI: 10.18632/oncotarget.20659
|View full text |Cite|
|
Sign up to set email alerts
|

Chidamide and decitabine can synergistically induce apoptosis of Hodgkin lymphoma cells by up-regulating the expression of PU.1 and KLF4

Abstract: Epigenetic abnormalities play important roles in the pathogenesis of Hodgkin lymphoma (HL). Highly expressed class I histone acetyltransferase (HDAC) and hyper-methylation of the promoter region of tumor suppressor genes have been demonstrated in Hodgkin lymphoma. In this paper, we investigated the synergistic effects of combination treatment of chidamide, a selective HDAC inhibitor, and decitabine, a demethylation agent, for HL cell lines and explored a new strategy for treating HL. The apoptosis rates, cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 31 publications
(43 reference statements)
0
7
0
Order By: Relevance
“…Immunogenic tumor cell death can drive the priming and clonal expansion of tumor-selective effector T cells, but it is ultimately the ability of cytolytic cells to kill tumor cells [ 61 , 62 ]. HBI-8000 can directly induce cell cycle arrest and apoptosis in a large number of tumor cells and tumor cell lines [ 26 ], (data not shown), but has also been shown to potentiate the cytotoxic activity of a number of anticancer agents by skewing the balance of expression toward pro-apoptotic proteins, and thus triggering the apoptotic response [ 18 , 20 32 , 63 – 65 ]. Based on the current data, as well as recent reports describing immunomodulatory activities of other class I selective HDACi [ 36 , 38 , 51 , 66 ], there might be at least 2 mechanisms at play: i) induction of immunomodulatory activities, including boosting antigen presentation and tumor cell recognition by immune effector cells and ii) immunogenic cell death [ 8 , 10 , 33 , 34 , 66 68 ], leading to the release of neoantigens and a potential increase in T cell priming and de novo generation of new tumor-selective effector T cell clones [ 69 , 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Immunogenic tumor cell death can drive the priming and clonal expansion of tumor-selective effector T cells, but it is ultimately the ability of cytolytic cells to kill tumor cells [ 61 , 62 ]. HBI-8000 can directly induce cell cycle arrest and apoptosis in a large number of tumor cells and tumor cell lines [ 26 ], (data not shown), but has also been shown to potentiate the cytotoxic activity of a number of anticancer agents by skewing the balance of expression toward pro-apoptotic proteins, and thus triggering the apoptotic response [ 18 , 20 32 , 63 – 65 ]. Based on the current data, as well as recent reports describing immunomodulatory activities of other class I selective HDACi [ 36 , 38 , 51 , 66 ], there might be at least 2 mechanisms at play: i) induction of immunomodulatory activities, including boosting antigen presentation and tumor cell recognition by immune effector cells and ii) immunogenic cell death [ 8 , 10 , 33 , 34 , 66 68 ], leading to the release of neoantigens and a potential increase in T cell priming and de novo generation of new tumor-selective effector T cell clones [ 69 , 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chidamide is a novel orally histone deacetylase inhibitor (HDACi), which has inhibitory activity against HDAC1, 2, 3, 10 (26). It has shown activity against several types of tumors in vitro and in vivo (26)(27)(28)(29)(30). Chidamide might suppress T lymphoma cell growth and promote the apoptosis of T lymphoma cells though interfering with the binding between histone and DNA (31).…”
Section: Discussionmentioning
confidence: 99%
“…CM induces anti-tumor effects through various mechanisms, depending on the type of cancer and its dose. These mechanisms include: i) Cell cycle arrest, CM arrests tumor cells at the G 0 /G 1 phase (12,16,25); ii) apoptosis induction, CM induces apoptosis by regulating the balance of pro- and anti-apoptotic genes, activating intrinsic apoptotic pathways (25); iii) suppression of cellular signaling pathways, CM inhibits the Janus kinase/STAT, PI3K/AKT and mitogen-activated protein kinase/JNK signaling pathways (16,19,26,27); iv) reactive oxygen species generation and induction of DNA damage (10,25); v) energy metabolism modulation, CM suppresses mitochondrial aerobic respiration by downregulation of mcl-1 (20); vi) activation of cellular antitumor immunity mediated by NK cells and antigen-specific cluster of differentiation 8-positive cytotoxic T lymphocytes (11); vii) reversion of transforming growth factor-β-induced epithelial-mesenchymal transition in tumor cells (28); and viii) upregulation of the tumor suppressor genes Spi-1 proto-oncogene and Krüppel-like factor-4 (29). In the present study, it was demonstrated that CM serves a role in suppressing the viability of MM cells.…”
Section: Discussionmentioning
confidence: 99%